Season of high adventure Edgar Snow in China - Thomas, S. B. (A Philip E. Lilienthal book, 1996)
"In 1928, Edgar Snow (1905-1972) set out to see the world, hoping to make his mark as a travel-adventure writer. Shanghai was to be a mere stopover, but Snow stayed on in China for thirteen years. The idealistic young Midwesterner became a journalist and developed close friendships with China's emerging revolutionary leaders. His 1938 classic, Red Star Over China, strongly influenced American views of the Chinese Communists and is still in print nearly sixty years later. S. Bernard Thomas's sensitive biography of Edgar Snow emphasizes the journalist's China experience and shows how he became involved in events along with reporting them. An epilogue takes up Snow's cold war travails and his often frustrating "bridge-building" efforts between China and the United States in the final decade of his life."--BOOK JACKET.